Adventitious root formation of hardwood and softwood stem cuttings of Pogostemon cablin (Nilam) as affected by different Indole-3-Butyric Acid (IBA) concentrations - Azrin, Nor Aina (2015)
Patchouli or its scientific name, Pogostemon cablin is an herbaceous perennial plant which is a native to India and Malaysia but nowadays, it is being cultivated in many tropical countries for the value of its essential oil which can be extracted to produce various profitable products. There are two methods in cultivating this plant which are by sexual or asexual propagation. Patchouli is a plant that rarely flowers and if it does, the flowering period is short and it is non-synchronized with other Patchouli plants. Because of this, propagation is done by asexual reproduction. Commonly, there are two methods of vegetative reproduction which are by stem cuttings and in vitro culture. Two studies were conducted in this project. Study one was done to observe the adventitious root formation of hardwood stem cuttings of Pogostemon cablin as affected by four different Indole-3-Butyric Acid (IBA) concentrations. These IBA concentrations were 0, 20, 40 and 60 mg/L. Study two was conducted to observe the adventitious root formation of softwood stem cuttings of Pogostemon cablin as affected by four different Indole-3-Butyric Acid (IBA) concentrations. These IBA concentrations were the same as the concentrations used in study one. The experimental design used in both studies was Randomized Complete Block Design (RCBD). Parameters used in both studies were the same which were days taken to root, root length, rooting percentage, root fresh weight and root dry weight. These experiments were done by treating a number of cuttings from study one and study two with these different IBA concentrations and were left to produce their root in a favourable condition over a period of 6 weeks. All data were analysed by Analysis of Variance (ANOVA) using Statistical Analysis System (SAS). Means comparison were used to determine the best IBA concentration treatments for both studies by using Less Significant Difference (LSD). In study one, result showed that 20 mg/L IBA concentration is the best treatment for hardwood stem cuttings of Pogostemon cablin. Study two proved that 60 mg/L IBA concentration is the best treatment for softwood stem cuttings of Pogostemon cablin.